No advanced retinopathy of prematurity stages 4 or 5 in a large high-risk German cohort. Issue 3 (30th June 2011) - Muether, Philipp S; Kribs, Angela; Hahn, Moritz; Schumacher, Jasmin; Eifinger, Frank; Kirchhof, Bernd; Roth, Bernhard; Fauser, Sascha
Abstract : Background: Retinopathy of prematurity (ROP) remains a major cause of juvenile blindness. As screening recommendations are refined, decreasing gestational age (GA) and birth weight (BW) constitute an increasing risk for ROP. This retrospective case series reviews the screening results of a very immature cohort in Germany. Methods: We conducted ROP screening according to the German guidelines of 1999: all preterm infants with a GA of <32 weeks and/or a BW of <1501 g, or with GA ≥32 weeks and postnatal oxygen treatment for >3 days, were assigned for screening. Dense laser coagulation was performed according to the current treatment criteria. Results: All 767 consecutive inborn (patients born at the Department of Neonatology, University Hospital of Cologne, Germany) preterm infants of a tertiary medical centre of maximum care underwent complete screening from 2001 to 2009. The treatment incidence was 7.0%. No preterm infant developed stage 4/5 ROP. Mean GA and BW of untreated/treated preterm infants were 28.4/24.6 weeks and 1109/635 g, respectively. Increasing treatment incidence was associated with lower GA, but not with lower BW in logistic regression analysis. Conclusion: In this very immature high-risk cohort, advanced stages 4 and 5 were avoided throughout 9 years of screening. We suggest three factors that contributed to this outcome: (1) strict adherence to current ROP screening and treatment guidelines; (2) prompt and very dense laser coagulation if necessary; and (3) a specialised neonatal intensive care unit with experience of very immature babies.